Historical and linguistic studies in literature related to the New Testament: Second series: linguistic and exegetical studies - Hoben, Allan; Herrick, Henry Martyn; Hobson, A.A.; Allen, H.F.; Thompson, E.F.; Norton, F.O.; Lewis, F.G.; Staudt, C.K.; Granberry, John Cowper; Wickes, Dean Rockwell; Ferguson, William Duncan; MacNeill, Harris Lachlan; et al. (University of Chicago, 1903)
Vol. 1. Pt. 1. Virgin birth / Allan Hoben. -- Pt. 2. Kingdom of God ... / H. M. Herrick. -- Pt. 3. Diatessaron of Tatian and the synoptic problem / A. A. Hobson. -- Pt. 4. Use of the infinitive in Polybius ... / H. F. Allen. -- Pt. 5. Metanoeo and Metamelei in Greek literature until 100 A.D. / E. F. Thompson. -- Pt. 6. Lexicographical and historical study of Diatheke / F. O. Norton. -- Pt. 7. Irenaeus testimony to the Fourth Gospel / F. G. Lewis. -- Pt. 8. Idea of the resurrection in the ante-Nicene period / C. K. Staudt.